Earth observation in archaeology: A brief review - Lei Luo; Xinyuan Wang; Huadong Guo; Xin Jia; Anchuan Fan (International Journal of Applied Earth Observations and Geoinformation, 2023)
Observing archaeological objects of interest (AOI) is pivotal to our understanding of past human-environment interactions, eco-social dynamics, and even the evolution of the ancient civilization. This has required development of advanced observational approaches to image and identify AOI at various circumstances and conditions. In the past decades, it has become very popular to employ passive and active sensing-based Earth observation (EO) technology to observe and analyse AOI all over the world. This has been promoted and highlighted by the surge of the observational data from different EO systems as well as the advances in digital image processing and analysis. Specifically, the employment of conventional single EO platform and transition to multi-platform integrated EO network provides significant improvement in the efficiency and accuracy of AOI prospecting together with diverse sensors and/or instruments. This paper aims to present a brief review on the use of EO-based solutions in AOI prospecting, with focus on the progress, application, advantage and limitations. Advances in EO science and technology have empowered archaeologists and EO specialists to explore the past in greater detail. Remote, proximal and in-situ networked and software-defined sensors that rely on the acquisition, processing and analysis of big EO data are more powerful than ever and continue to let us see the unseen - that is, new knowledge about the past and who are we.